The Coronation of the Young King in 1170 - Heslin, Anne (Studies in church history, 1965)
The coronation of Henry II’s eldest son, the younger Henry, in Westminster Abbey on 14 June 1170 was an event of the highest significance. The ceremony was performed by Roger, archbishop of York, assisted by the bishops of London and Salisbury, in the presence of Henry II, but in the absence, and against the will, of the exiled archbishop of Canterbury, Thomas Becket, and in defiance of the commands of the pope, Alexander III. The coronation itself has an intrinsic interest: the practice of crowning an heir in his father’s lifetime, though customary in France, and occurring at times in the German and Byzantine empires, was unusual in England.